Liver Tuberculosis Presenting as an Uncommon Cause of Pyrexia of Unknown Origin: Positron Emission Tomography/Computed Tomography Identifies the Correct Site for Biopsy - Yu, Hai-Ying (Med Princ Pract, 2014)
OBJECTIVE: To identify the correct site to biopsy in a case of pyrexia of unknown origin (PUO) caused by hepatic tuberculosis (TB). CLINICAL PRESENTATION AND INTERVENTION: A 58-year-old man who developed hepatic TB presented with PUO. Ultrasonography (US) and computed tomography (CT) of the abdomen showed only calcifications in the liver, and positron emission tomography (PET)/CT showed diffuse increased metabolic activity in addition to focal areas of increased activity. A diagnosis of hepatic TB was confirmed by histological examination of liver tissues and interferon-γ release assays (IGRAs of T-SPOT/TB). The patient was treated with 4 anti-tubercular therapies (rifampicin, isoniazid, ethambutol and pyrazinamide). At the 3-month follow-up, the patient was disease free as confirmed by abdominal US. CONCLUSION: PET/CT was helpful in identifying a site to biopsy that led to the correct diagnosis.